1980
DOI: 10.1007/bf01967493
|View full text |Cite
|
Sign up to set email alerts
|

Social class discrimination in the schooling process: Myth and reality

Abstract: A recurrent finding is that student's social class is related to school performance (EeUs et al., 1951 ;Heimann and Schenk, 1954;Deutsch, 1960;Coleman et aL, 1966; Fleishmann Report, 1972) and to educational attainment (Folger and Nam, 1967;Spady, 1967;SeweU, 1971, U_S. Bureau of the Census, 1973 Treiman and TerreU, 1975). A variety of causative factors have been suggested. This paper will explore only two: social class bias of school personnel and the relationship of the meritocratic ideology of the schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In a study using national data, Fligstein and Fernandez (1985) found that both Hispanic and White students who attended schools having a high percentage of Hispanics were more likely to have experienced grade delay and to drop out of school. Other studies have shown that Hispanic students are very often "tracked" in high school general or vocational programs, and very rarely placed in college preparatory programs (Amato, 1980;arum, 1986). This practice places Hispanic students at a clear disadvantage because most public high school students in vocational programs do not meet admissions requirements for four-year colleges.…”
Section: Counseling Applicationsmentioning
confidence: 99%
“…In a study using national data, Fligstein and Fernandez (1985) found that both Hispanic and White students who attended schools having a high percentage of Hispanics were more likely to have experienced grade delay and to drop out of school. Other studies have shown that Hispanic students are very often "tracked" in high school general or vocational programs, and very rarely placed in college preparatory programs (Amato, 1980;arum, 1986). This practice places Hispanic students at a clear disadvantage because most public high school students in vocational programs do not meet admissions requirements for four-year colleges.…”
Section: Counseling Applicationsmentioning
confidence: 99%